2012
DOI: 10.3390/ijms130911610
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Aspects of Colloidal Interactions in Mixed Systems of Liposome and Inorganic Nanoparticle and Their Applications

Abstract: In the past few years, growing attention has been devoted to the study of the interactions taking place in mixed systems of phospholipid membranes (for instance in the form of vesicles) and hard nanoparticles (NPs). In this context liposomes (vesicles) may serve as versatile carriers or as a model system for biological membranes. Research on these systems has led to the observation of novel hybrid structures whose morphology strongly depends on the charge, composition and size of the interacting colloidal spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 195 publications
(320 reference statements)
9
99
0
Order By: Relevance
“…The POPC lipids used in our study have an externally situated lipid polar head (the trimethylammonium group) that is positively charged and faces the aqueous glucose solution. 31 24 Also, in our previous study 46 using C 60 NPs, altered global membrane curvature was observed to be the cause of vesicle bursting after incubation in NP suspensions. Laurencin et al 25 demonstrated that the surface properties of NPs control the interaction between two oppositely charged species (GUVs and functionalized maghemite NPs), which is not ruled by global attraction of opposite charges as expected.…”
Section: Mlvs After Incubation In Np Suspensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The POPC lipids used in our study have an externally situated lipid polar head (the trimethylammonium group) that is positively charged and faces the aqueous glucose solution. 31 24 Also, in our previous study 46 using C 60 NPs, altered global membrane curvature was observed to be the cause of vesicle bursting after incubation in NP suspensions. Laurencin et al 25 demonstrated that the surface properties of NPs control the interaction between two oppositely charged species (GUVs and functionalized maghemite NPs), which is not ruled by global attraction of opposite charges as expected.…”
Section: Mlvs After Incubation In Np Suspensionsmentioning
confidence: 99%
“…24,46 Second, a local change in membrane curvature followed by indentation of NPs and their agglomerates into the membrane could result in NP-membrane encapsulation, or internalization. 13,20,24,60 Published reports 20,24,58 indicate that membrane wrapping and encapsulation are consequences of interplay between the mean bending modulus of the bilayer and the adhesion energy per unit area. The large aggregates could not be encapsulated due to geometric restriction dictated by the large relative volume and spherical shape of GUVs.…”
Section: Mlvs After Incubation In Np Suspensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] The adsorption of such nanoparticles on vesicle membranes, forming decorated vesicle structures, is believed to allow for the stabilisation of the vesicle dispersion by introducing repulsive electrostatic interactions between the vesicle-nanoparticle complexes. However, considering the potential cytotoxicity of nanoparticles 26 and their various ways of interacting with the lipid membrane, 27 further fundamental studies on this mixed system are necessary in order to gain a systematic understanding of this effect of vesicle stabilisation, which will depend on the details of the interaction between nanoparticles and the vesicle membrane, as well as on the nature of the phospholipid membrane.…”
Section: -22mentioning
confidence: 99%
“…a limited number of biomolecular components, and are amenable to biophysical methods that measure, for example, lipid order or membrane permeability. [20][21][22][23][24][25][26] In recent years, the lipid bilayer methodology has started to be applied to the study of ENM-membrane interactions, 27,28 primarily in the context of establishing structure-function relationships for nanotoxicology assessment. 29,30 For example, electrical measurements of ENM-exposed suspended bilayers have shown that quantum dots, carbon nanotubes and polystyrene or silica nanospheres render bilayers permeable to ions, indicating a nanoparticle-induced perturbation of the bilayer structure.…”
Section: Introductionmentioning
confidence: 99%